Evaluasi Desain Tower Truck Shipping Out Station dan Analisis Keselamatan Kerja Proses Penerpalan dengan Metode HIRADC Pada PT XYZ - , Muhammad Afif Ramadhan; , Rusindiyanto (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
Tarpaulin work is work carried out at height to protect a product. Tarpaulin work is a high-risk activity if you are not equipped with the appropriate safety equipment. The risk of serious injury is high because of the height at which tarpaulin work is carried out. This research resulted in an evaluation of the Tower Truck Discharge Station, a new infrastructure to support safety in the tarpaulin process. Based on the results of data processing based on truck height variability, it is recommended that the ideal tower height of approximately 300 cm be established as a reference. With this tower height, the distance that workers have to cover when descending into the truck bed is reduced to only 14 cm, while the distance that workers have to cover when climbing onto the truck is approximately 18 cm. It was also found that when identifying and assessing hazards during the tarpaulin process, accidents caused by slippery steps on the truck bed were included in the low-risk category, although they still required vigilance. Factors such as climbing or descending high steps (2-3 metres), working at height, exposure to extreme weather conditions (heat, wind, rain) and exposure to dust or hazardous materials were placed in the medium risk category because they increase the potential for accidents. Meanwhile, the risk from slippery fertiliser piles is classified as high risk because it has the potential to cause fatal accidents, so serious precautions are needed.